Efficient metal-free green syntheses of 4H-chromenes and 3-amino alkylated indoles using a reusable graphite oxide carbocatalyst under aqueous and solvent-free reaction conditions. (1st June 2022) - Kyndiah, Lenida; Sarkar, Fillip Kumar; Gupta, Ajay; Pal, Amarta Kumar
Abstract : Graphite oxide was employed as a reusable catalyst for the synthesis of 4 H -chromenes and 3-amino alkylated indoles in aqueous and solvent-free reaction conditions. Abstract : Graphite oxide (GO) was utilized for the one-pot three-component syntheses of pharmaceutically important 4 H -chromenes and 3-amino alkylated indoles in water and solvent-free reaction conditions, respectively. Spectroscopic techniques such as FT-IR, XPS, SEM, TEM, SAED, EDX, PXRD, Raman, and TGA confirmed the formation and thermal stability of GO. These protocols provide green and sustainable reaction conditions, including excellent catalytic activity, good to excellent yield of the products, reusability of the catalyst, high functional group tolerance, and Gram-scale synthesis. Further, the present methodologies exclude the problems of metal toxicity, metal waste disposal, metal contamination in the products, and the use of volatile organic solvents.